Pengaruh Pengawas Menelan Obat terhadap Kepatuhan Penderita TB Paru dalam Menelan Obat - Frans, Fierny Bethony; Sitompul, Monalisa (Universitas Malahayati, 2023)
ABSTRACT According to the WHO Global TB Report in 2020, tuberculosis is included in the list of the 10 main causes of death worldwide, including in Indonesia. From the observations of researchers at the TB DOTS (Direct Observe Treatment Shortcourse) Polyclinic at Bandung Adventist Hospital, it was found that there was an increase in cases of pulmonary TB in adults, the number continues to increase every month. One of the factors that influence patients to adhere to swallowing drugs is the existence of a Drug Swallowing Supervisor (PMO). Drug Swallowing Supervisor is a component in the Directly Observed Treatment (DOT) which plays a role in monitoring the drug swallowing of pulmonary TB patients with the aim that the patient wants to take the medicine that has been recommended. The research design was a Pre-Experimental Design using Static Group Comparison with the experimental group being given the Drug Swallowing Supervisor (PMO) intervention and the control group without the Drug Swallowing Supervisor (PMO) intervention. The results of this study found that 10 aspects of the drug swallowing supervisor questionnaire had been carried out obediently (90%) and 5 aspects had not been carried out optimally (85-88%). Analysis of patient adherence to swallowing medication through the Morisky Medication Adherence Scale shows 5 aspects with good knowledge by patients taking medication (80%) and 3 aspects of sufficient knowledge (60%). It was concluded that from the PMO questionnaire which was divided into four aspects including supervision of taking medication, the role of the supervisor taking medication, the supervisor's task of swallowing medication, the information conveyed by the Medication Supervisor with an average of 93.4% - 100%, greatly determines pulmonary TB patient adherence in swallow medicine. With the Medication Supervisor it is hoped that it can prevent TB sufferers from experiencing drug withdrawal, drug resistance and MDR TB. Suggestion: increase the influence of drug taking supervisors so that pulmonary TB sufferers are obedient in swallowing TB medication so that when traveling or leaving the house they don't forget to take medication Keywords: Medication Supervisor, Pulmonary TB, Medication Swallowing Compliance. ABSTRAK Menurut WHO Global TB Report tahun 2020 menyatakan bahwa penyakit Tuberkulosis masuk dalam daftar 10 penyebab utama kematian di seluruh dunia temasuk di Indonesia. Dari hasil observasi peneliti di Poli TB DOTS (Direct Observe Treatment Shortcourse) RS Advent Bandung, ditemukan adanya peningkatan kasus TB paru pada orang dewasa, jumlahnya terus bertambah setiap bulannya. Salah satu faktor yang mempengaruhi penderita patuh menelan obat adalah dengan adanya Pengawas Menelan Obat (PMO). Pengawas Menelan Obat adalah suatu komponen yang ada pada Directcly Observed Treatment (DOT) yang berperan dalam pengawasan menelan obat pasien TB paru dengan tujuan agar pasien mau minum obat yang telah dianjurkan. Desain penelitian ini adalah PreExperimenta Design dengan menggunakan Static grup comparison dengan kelompok eksperimen diberikan intervensi Pengawas Menelan Obat (PMO) dan kelompok control tanpa intervensi Pengawas Menelan Obat (PMO). Hasil penelitian ini didapatan bahwa 10 aspek kuisioner pengawas menelan obat sudah dilakukan dengan patuh (90%) dan 5 aspek belum dilakukan secara maksimal (85-88%). Analisa kepatuhan penderita menelan obat melalui Morisky Medication Adherence Scale menunjukan 5 aspek dengan pengetahuan yang baik oleh penderita minum obat (80%) dan 3 aspek pengetahuan cukup maksimal (60%). Disimpulkan bahwa dari kuesioner PMO yang terbagi dalam empat aspek meliputi pengawasan minum obat, peran pengawas menelan obat, tugas pengawas menelan obat, informasi yang disampaikan Pengawas Minum Obat dengan rata-rata 93,4% - 100%, sangat menentukan penderita TB paru patuh dalam menelan obat. Dengan adanya Pengawas Minum Obat diharapkan dapat mencegah penderita TB mengalami putus obat, resistensi obat maupun TB MDR. Saran: meningkatkan lagi pengaruh pengawas minum obat agar penderita TB paru patuh dalam menelan minum obat TB sehingga pada saat bepergian atau meninggalkan rumah tidak lupa untuk membawa obat. Kata Kunci: Pengawas Minum Obat, TB Paru, Kepatuhan Menelan.